Barrierfree Mobility in Asia and Europe. Barrierefreie Mobilität als Planungsgegenstand in Europa und Asien. - (:unkn) unknown (My University, 2007)
Dokumentation des Workshops "Accessibility for all - Barrierfree Mobility" im Rahmen der "Asien-Pazifik-Wochen" in Berlin, September 2007. Einzelbeiträge des Workshops: Wulf-Holger Arndt: Barrierfree mobility - accessibility in transportation planning and transport system / Naohiko Hibino: Japan - aging society and change of mobility of metropolitan Area / Wang Hongyan: China - multianalysis of road traffic accident research / Jürgen Roß: Information - public transport travel information for mobility impaired people through VBB's travel plan / Feng Liguang: China - transportation management and changing society / Manfred Rentzsch: Vehicles - barrierfree accessibility to vehicles of local public and long distance traffic / Hiroshi Kitagawa: Japan - the practice of universal design and transport / Jan Schlaffke: Buildings - barrierfree accessibility and movement in buildings and interfaces in transport system.

Modern societies are characterized by an aging population as a result of the shrinking birth rate and the sagging fertility rate. This development requires new constructional, informational and technical standards regarding mobility. Prognoses predict that beside the trend towards aging populations there will be a significant shrinkage of the spatial structure of settlement within the next decades. This process is not consistent in a regional and temporal way. Especially in prospering rural areas migration and aging exist in parallel. Immigration and certain socio-demographic effects (e.g. to start a family in a high age) may relieve the main trend of shrinkage. In particular, this effect is valid for metropolises. To provide mobility for everyone in a long term under these heterogeneous conditions is a new scientific and economic challenge. The social change of our society will also impact the mobility design in the future. Elder people will have a lower income. Wealth will not be described only by rate of consumption. This is also a chance for creation sustainable life styles. Due to these developments the challenges for mobility design are versatile and complex. "Accessibility for all" or "Design for all" describes a new approach to ensure social inclusion of everyone under these conditions of changing society.
Keywords: Verkehr; Technische Infrastruktur; Schrumpfung; Verkehrsplanung; Mobilität; Öffentlicher Verkehr; Erreichbarkeit; Barrierefreiheit